Analisis pendapatan usaha budidaya ikan putih selama covid-19 di Kelurahan Petoaha Kecamatan Abeli Kota Kendari Provinsi Sulawesi Tenggara - Saputra, Ade; Nurdiana A; Piliana, Wa Ode; La Ola, La Onu (Jurnal Sosial Ekonomi Perikanan, 2024)
This research was conducted in Petoaha Village, Abeli District, Kendari City, Southeast Sulawesi Province from January to February 2022. This study aims to determine the financial vulnerability of cultivation business actors during Covid-19 in Petoaha Village, Abeli ​​District, Kendari City, Southeast Sulawesi. The selection of research locations was carried out purposively. The study used the determination of respondents by census and obtained as many as 11 people. Data obtained through interviews based on questionnaires. The data collected is age, education level, business experience, total income, income and also the total expenditure incurred in one harvest. The data analysis used in this research is income analysis and descriptive analysis with the formula TC=TFC+TVC, TR = Q.P, Π= TR-TC. The results of the analysis show that the average income of the White Fish Cultivation Business in Petoaha Village is Rp21,571,182 in one harvest/year, where the average revenue is Rp38,848,182 in one harvest/year, while the average total cost is Rp13.004.273 in one harvest/year. This shows that the average income from cultivation is quite large in one harvest in Petoaha Village, Abeli ​​District, Southeast Sulawesi Province.